SMASH SKILL LEVEL OF MALE ATHLETES OF UKM VOLLEYBALL BINA BANGSA GETSEMPENA UNIVERSITY BANDA ACEH - Salbani Salbani; Septi Hariansyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to analyze the level of smash skills in male athletes of Volleyball UKM Universitas Bina Bangsa Getsempena Banda Aceh. This study involved 12 athletes with a focus on three main aspects of smash skills, namely hitting speed, ball direction accuracy, and jump height. The method used is descriptive quantitative, with data collection through direct measurement of each relevant variable. Based on the results of the study, the average athlete's hitting speed is in the Good category (18.0–19.4 m/s), with most athletes showing effective hitting abilities. In terms of ball direction accuracy, 41.7% of athletes are in the Very Good category (≥ 85%), indicating high precision ability in directing the ball when smashing. For jump height, 33.3% of athletes are in the Very Good category (≥ 70 cm), which supports the effectiveness of smashes in avoiding opponent blocks. Overall, the majority of athletes show solid smash skills, although there is still room for improvement in the aspects of speed, accuracy, and jump height. This study provides useful insights for improving training programs in order to improve athlete performance and maximize their potential in matches.